Human sensory-like neuron cultivation—An optimized protocol - Schottmann, Nicole Michelle; Grüner, Julia; Bär, Frederik; Karl-Schöller, Franziska; Oerter, Sabrina; Üçeyler, Nurcan (Frontiers in Neuroscience, 2024)
IntroductionReprogramming of human-induced pluripotent stem cells (iPSCs) and their differentiation into specific cell types, such as induced sensory-like neurons (iSNs), are critical for disease modeling and drug testing. However, the variability of cell populations challenges reliability and reproducibility. While various protocols for iSN differentiation exist, the development of non-iSN cells in these cultures remains an issue. Therefore, standardization of protocols is essential. This study aimed to improve iSN culture conditions by reducing the number of non-iSN cells while preserving the survival and quality of iSNs.MethodsiSNs were differentiated from a healthy control iPSC line using an established protocol. Interventions for protocol optimization included floxuridine (FdU) or 1-β-D-arabinofuranosyl-cytosine hydrochloride (AraC) treatment, magnetic-activated cell sorting (MACS), early cell passaging, and replating. Cell viability and iSN-to-total-cell-count ratio were assessed using a luminescent assay and immunocytochemistry, respectively.ResultsPassaging of cells during differentiation did not increase the iSN-to-total-cell-count ratio, and MACS of immature iSNs led to neuronal blebbing and reduced the iSN-to-total-cell-count ratio. Treatment with high concentrations and prolonged incubation of FdU or AraC resulted in excessive cell death. However, treatment with 10 μM FdU for 24 h post-differentiation showed the most selective targeting of non-iSN cells, leading to an increase in the iSN-to-total-cell count ratio without compromising the viability or functionality of the iSN population. Replating of iSNs shortly after seeding also helped to reduce non-iSN cells.ConclusionIn direct comparison with other methods, treatment with 10 μM FdU for 24 h after differentiation shows promise for improving iSN culture purity, which could benefit downstream applications in disease modeling and drug discovery. However, further investigations involving multiple iPSC lines and optimization of protocol parameters are warranted to fully exploit the potential of this method and enhance its reproducibility and applicability. Overall, this study provides valuable insights into optimizing culture conditions for iSN differentiation and highlights the importance of standardized protocols in iPSC-based research.